International feasibility trial on the use of an interactive mobile health platform for cardiac rehabilitation: protocol of the Diversity 1 study - Gonzalez-Garcia, Manuel Cruz (BMJ Health Care Inform, 2019)
INTRODUCTION: The implementation of home-based cardiac rehabilitation has demonstrated potential to increase patient participation, but the content and the delivering of the programmes varies across countries. The objective of this study is to investigate whether an Australian-validated mobile health (mHealth) platform for cardiac rehabilitation will be accepted and adopted irrespectively from the existing organisational and contextual factors in five different European countries. METHODS AND ANALYSIS: This international multicentre feasibility study will use surveys, preliminary observations and analysis to evaluate the use and the user’s perceptions (satisfaction) of a validated mHealth platform in different contextual settings. ETHICS AND DISSEMINATION: This study protocol has been approved by the Australian research organisation CSIRO and the respective ethical committees of the European sites. The dissemination of this trial will serve as a ground for the further implementation of an international large randomised controlled trial which will contribute to an effective global introduction of mHealth into daily clinical practice.